Recurrent Implantation Failure - Kolibianakis, Efstratios M.; Venetis, Christos A. (Milton : CRC Press LLC, 2019)
Implantation is a complex phenomenon, still not thoroughly understood, involving the embryo and the endometrium. Successful implantation is considered to stem from an efficient combination of various embryo and/or maternal factors. Repeated failure of any of these factors or of their combination might decrease the chance of implantation and eventually lead to recurrent implantation failure. Despite technological advances, only about a quarter of In Vitro Fertilization procedures will result in live birth, leading many couples to experience multiple failures. This text from international experts explores the various factors at play and offers a helpful summary of the state of knowledge to help guide clinicians in their management of this complex and important problem. Contents: What is Recurrent Implantation Failure? * The psychosocial aspects of recurrent implantation failure * The role of life-style factors in RIF * Endocrine causes of recurrent implantation failure * Congenital uterine anomalies and recurrent implantation failure * Immunological causes of recurrent implantation failure * Acquired uterine conditions, reproductive surgery, and RIF? * Thrombophilia: diagnosis and management in women with recurrent implantation failure * Andrological causes of RIF * Diagnostic evaluation of RIF? (Modalities and algorithm) * Optimizing embryo culture for RIF? * Optimizing endometrial receptivity for patients with recurrent implantation failure: The role of progesterone on the day of triggering final oocyte maturation * Is there a role of follicular phase LH and E2 on the day of triggering final oocyte maturation for embryo implantation? * Manipulating the endometrium: Can RIF be managed by inducing endometrial inflammation or by the use of novel research therapies * The embryo in RIF: Genetic selection and strategies for improving its implantation potential * Is oocyte donation efficient in patients with RIF? * Sperm donation and RIF? * Optimizing embryo transfer technique for RIF management * Proposed management of patients with recurrent implantation failure and directions for future research * When should patients abandon treatment?
OCLC-licensed vendor bibliographic record.
Keywords: Fertilization in vitro, Human; MEDICAL -- Gynecology & Obstetrics; MEDICAL -- Reproductive Medicine & Technology; MEDICAL -- Endocrinology & Metabolism